Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1111/j.1365-2036.2004.02152.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid improvement of bone metabolism after infliximab treatment in Crohn's disease

Abstract: SUMMARY Background: 1Crohn's disease is associated with low bone mineral density and altered bone metabolism. Aim: To assess the evolution of bone metabolism in Crohn's disease patients treated with infliximab. Methods: We studied 71 Crohn's disease patients treated for the first time with infliximab for refractory Crohn's disease. Biochemical markers of bone formation (type-I procollagen N-terminal propeptide, bone-specific alkaline phosphatase, osteocalcin) and of bone resorption (C-telopeptide of type-I col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
2
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 58 publications
6
51
2
3
Order By: Relevance
“…(31) Recent studies in adults with Crohn's disease have shown significant changes in biomarkers of bone metabolism with anti TNF-α therapy. (32,33) Of these, Franchimont et al reported decreased bone formation and increased bone resorption markers at baseline when compared with healthy controls. (33) The observation that bone formation was low and bone resorption was high prior to treatment with anti TNF-α therapy is consistent with our observation of low BSAP and high DPD in Crohn's disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(31) Recent studies in adults with Crohn's disease have shown significant changes in biomarkers of bone metabolism with anti TNF-α therapy. (32,33) Of these, Franchimont et al reported decreased bone formation and increased bone resorption markers at baseline when compared with healthy controls. (33) The observation that bone formation was low and bone resorption was high prior to treatment with anti TNF-α therapy is consistent with our observation of low BSAP and high DPD in Crohn's disease.…”
Section: Discussionmentioning
confidence: 99%
“…(32,33) Of these, Franchimont et al reported decreased bone formation and increased bone resorption markers at baseline when compared with healthy controls. (33) The observation that bone formation was low and bone resorption was high prior to treatment with anti TNF-α therapy is consistent with our observation of low BSAP and high DPD in Crohn's disease. The observation that greater disease activity (PCDAI score) was independently associated with greater reductions in BSAP levels in our study further supports the hypothesis that inflammatory cytokines contribute to suppressed bone formation in Crohn's disease.…”
Section: Discussionmentioning
confidence: 99%
“…These effects seem to be independent of whether the patients are classified as responders or non-responders to infliximab treatment based on clinical scores, and of whether the patients are on steroid therapy [16][17][18]. Patients who received infliximab have also been shown to have increased BMD based on DXA findings [21][22][23].…”
Section: Introductionmentioning
confidence: 93%
“…To date, data describing the effects of in vivo TNF-α inhibition on general bone metabolism in patients with IBD are still limited and restricted to infliximab treatment [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…DeBoer et al [126] have shown, using a dextran sodium sulfate induced colitis model, that mice treated with anti-TNF-α antibodies demonstrated a partial normalization of pubertal timing coincident with decreased systemic inflammation. Bone metabolism is also positively affected by infliximab, at least in the short-term, manifested by improved bone formation markers [127,128].…”
Section: Biologic Treatmentmentioning
confidence: 99%